1998
DOI: 10.1002/(sici)1096-9861(19981207)402:1<93::aid-cne7>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Efferent and collateral organization of paratrigeminal nucleus projections: An anterograde and retrograde fluorescent tracer study in the rat

Abstract: The paratrigeminal nucleus (PTN) receives primary visceral afferent projections through cranial nerves IX and X and somatic afferent projections through cranial nerve V and dorsal roots as far caudally as C7. Pressure injections of the anterograde tracer tetramethylrhodamine dextran into the PTN in the rat resulted in bilateral labeling in the nucleus of the tractus solitarius, dorsal motor nucleus of the vagus nerve, and parabrachial nucleus. Anterograde labeling in the parabrachial nucleus was strongest in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…Only one report (Cechetto et al, 1985) has mentioned the existence of projections fron the spinal trigeminal nucleus caudalis to the PBm. However, the representative injection site in this study spread out into the paratrigeminal nucleus, a structure that has been shown to project to the PBm (Cechetto et al, 1985; Herbert et al, 1990; Feil and Herbert, 1995; Saxon and Hopkins, 1998). Thus, within the trigeminal system, projections to the PBm and the PBvl seem to be unique to the Sp5O.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Only one report (Cechetto et al, 1985) has mentioned the existence of projections fron the spinal trigeminal nucleus caudalis to the PBm. However, the representative injection site in this study spread out into the paratrigeminal nucleus, a structure that has been shown to project to the PBm (Cechetto et al, 1985; Herbert et al, 1990; Feil and Herbert, 1995; Saxon and Hopkins, 1998). Thus, within the trigeminal system, projections to the PBm and the PBvl seem to be unique to the Sp5O.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a high proportion of neurons doubly labeled with fluorogold following injection into the parabrachial region and Fos protein subsequent to noxious tooth pulp stimulation has been observed in the D‐Sp5O (Allen et al, 1996). Therefore, in addition to the spinal trigeminal nucleus caudalis (Feil and Herbert, 1995) and the paratrigeminal nucleus (Feil and Herbert, 1995; Saxon and Hopkins, 1998), the D‐Sp5O might provide an additional source of trigeminal nociceptive inputs to the PBem. This pathway could be responsible, at least in part, for the arousal response to aversive and/or noxious events (Halsell and Travers, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…An exception to this relationship was the dPa5 region, where few ERα-positive neurons were seen, yet TMJ-evoked Fos-LI was significantly greater in HE2 than LE2 rats. The dPa5 region receives significant direct afferent input from visceral afferents as well as trigeminal nerves and is thought to be important for sensory-autonomic integration (Saxon and Hopkins, 1998; Caous et al, 2001). These data do not, however, exclude the possibility that E2 acted on peripheral tissues or modified the properties of trigeminal ganglion (TG) cells.…”
Section: Discussionmentioning
confidence: 99%
“…2), possibly via convergent input from capsaicinsensitive trigeminal fibers. Gustatory NTS neurons are known to be excited by innocuous somatosensory stimuli (Ogawa et al, 1984(Ogawa et al, , 1988Hayama et al, 1985;Travers and Norgren, 1995), and anatomical studies have shown projections to the NTS from trigeminal afferents (Jacquin et al, 1982;Hamilton and Norgren 1984;Marfurt and Rajchert, 1991) as well as from neurons in the Vc and paratrigeminal nucleus (Menétrey and Basbaum, 1987;Saxon and Hopkins, 1998). A second possibility is that some gustatory NTS units receive input directly from capsaicinsensitive chorda tympani fibers (Okuni, 1977), although other studies indicate that chorda tympani fibers are not capsaicin sensitive (Silver et al, 1985;Hiura et al, 1990).…”
Section: Nts Unit Responses To Capsaicinmentioning
confidence: 99%
“…Finding this to be the case, we also investigated whether the suppression occurs at a central or peripheral site. A substrate for central trigeminal modulation of gustatory processing in the NTS is supported by anatomical studies showing projections to the NTS from branches of trigeminal afferents (Jacquin et al, 1982;Whitehead and Frank, 1983;Hamilton and Norgren, 1984) as well as from neurons in Vc and paratrigeminal nucleus (Menétrey and Basbaum, 1987;Saxon and Hopkins, 1998). Some trigeminal fibers projecting to the NTS contain substance P (South and Ritter, 1986), which modulates NTS responses to NaCl (Davis and Smith, 1997).…”
Section: Introductionmentioning
confidence: 95%